The Ferric Citrate Uptake System Encoded in a Novel blaCTX–M–3- and blaTEM–1-Harboring Conjugative Plasmid Contributes to the Virulence of Escherichia coli - Huang, Wen-Chun; Wong, Min-Yi; Wang, Ssu-Han; Hashimoto, Masayuki; Lin, Meng-He; Lee, Mei-Feng; Wu, Jiunn-Jong; Wang, Ming-Cheng; Lin, Wei-Hung; Jeng, Shuen-Lin; Wang, Jiun-Ling; Chen, Ya-Lei; et al. (Frontiers in Microbiology, 2021)
Escherichia coli is one major cause of bacterial infections and can horizontally acquire antimicrobial resistance and virulence genes through conjugation. Because conjugative plasmids can rapidly spread among bacteria of different species, the plasmids carrying both antimicrobial resistance and virulence genes may pose a significant threat to public health. Therefore, the identification and characterization of these plasmids may facilitate a better understanding of E. coli pathogenesis and the development of new strategies against E. coli infections. Because iron uptake ability is a potential virulence trait of bacteria, we screened for E. coli conjugative plasmids able to confer both iron uptake ability and ampicillin resistance. The plasmid pEC41, which was derived from the bacteremia clinical isolate EC41, was identified. EC41, which carried the fimH27 allele, belonged to sequence type (ST) 405 and phylogroup D. According to the sequencing analyses, pEC41 was 86 kb in size, and its backbone structure was almost identical to that of another highly conjugative plasmid, pCTX-M3, in which the extended-spectrum β-lactamase gene blaCTX-M-3 was originally identified. pEC41 carried blaCTX-M-3 and blaTEM-1. The ferric citrate uptake (fec) system was identified in pEC41 and was responsible for conferring iron uptake ability. The fec system contributes to the pathogenesis of EC41 in systemic infections but not in urinary tract infections (UTIs). However, this system promoted competitive fitness of a cystitis-associated clinical isolate to colonize urinary tracts. Additionally, the distribution of the fec system was related to E. coli isolates associated with human bacteremia and UTIs. In summary, the present study identified a novel conjugative plasmid, pEC41, which conferred both antimicrobial resistance and an extra iron uptake ability to E. coli. The iron uptake ability was encoded in the fec system and contributed to E. coli pathogenesis. This study is the first to show that the fec system is a virulence factor in E. coli.